2019
DOI: 10.1002/chem.201902927
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Controlled Stereodivergent Synthesis of 2,2′‐Biflavanones Promoted by Samarium Diiodide

Abstract: In this work,t he first exampleo faradical stereodivergent reactiond irected towardst he stereoselective synthesis of both (R*,R*)-and (R*,S*)-2,2'-biflavanones promoted by samarium diiodide is reported. Control experiments showedt hat the selectivity of this reaction was exclusively controlled by the temperature. It was possible to generate av ariety of 2,2'-biflavanones bearing different substitution patterns at the aromatic ring in good-toquantitative yields, being both stereoisomerso ft he desired compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In the presence of SmI 2 , 2,2 0 -bichromone 10 was obtained in 53% yield. 16 The Cucatalyzed alkynylation of 3a afforded 11 with good efficiency. 17 Using DTBP as the oxidant, 2-alkylated chromanone 12 was achieved in 64% yield using cyclohexane as a valid alkyl source.…”
mentioning
confidence: 99%
“…In the presence of SmI 2 , 2,2 0 -bichromone 10 was obtained in 53% yield. 16 The Cucatalyzed alkynylation of 3a afforded 11 with good efficiency. 17 Using DTBP as the oxidant, 2-alkylated chromanone 12 was achieved in 64% yield using cyclohexane as a valid alkyl source.…”
mentioning
confidence: 99%
“…Interestingly, when we performed the reaction at 140 °C, 4a was not detected and the aromatized product 5a was obtained in 62% yield instead. These experimental observations indicated that it may be possible to develop a temperature-switchable synthetic protocol 20 for the synthesis of either 4a or 5a in a chemoselective manner. Furthermore, a variety of different Brønsted and Lewis acids were found to impove the yield of 4a at 110 °C, and HOAc at 2.0 equiv.…”
Section: Resultsmentioning
confidence: 95%
“…Aza-pinacol coupling of benzylideneaniline 5 proceeded under the optimal conditions to afford 1,2-diamine 6 in 85% yield. Flavone 7 can also be reduced to provide 2,2′-biflavanone 8 in 47% yield . We further investigated the reductive bond cleavage reactions.…”
Section: Resultsmentioning
confidence: 99%